Réponses

2014-04-10T22:14:01+02:00
Ex6:
Factoriser :
A= (2x+4)² +(2x+4)(4x-1)
A= (2x+4) [(2x+4)+(4x-1)]
A= (2x+4)(2x+4+4x-1)
A= (2x+4)(6x +3)
Résoudre A=0
A= (2x+4)(6x+3)
2x+4= 0
2x=-4
x= - 4/2
x= -2

6x+3=0
6x= - 3
x=- 3/6
x= - 1/2
donc l'équation a deux solutions : -2 et -1/2
Ex 7:
B= (3x-5)(x+1) -(2x+4)(3x-5)
Factoriser B:
B= (3x-5)[(x+1)-(2x+4)]
B= (3x-5)(x+1 -2x -4)
B= (3x-5)(-x - 3)

Résoudre B=0
B= (3x-5) (-x - 3)=0
3x-5=0
3x=5
x= 5/3

-x- 3=0
-x=3
x= -3
Donc l'équation a deux solutions : 5/3 et - 3